PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DAN KINERJA PASAR PADA PERUSAHAAN MULTINASIONAL DI INDONESIA - Puji Lestari; Sri Harmeidiyanti; Uswatun Hasanah; Rini Widianingsih (InFestasi, 2013)
This research aims to investigate the effect of intellectual capital to financial performance and market performance at multinational companies listed in Indonesia Stock Exchange. Research population consists of 65 listed companies. Samples were taken by purposive sampling method which is 51 companies. The analytical technique used in this research is simple linear regression.It is found that intellectual capital is not affecting financial performance and market performance of multinational companies in Indonesia. It suggests that intellectual capital has not been able to create high value added of the company yet. This research also suggests that market is not appraise the company any higher when the company has higher intellectual capital.